Description of Nutritional Status of Pregnant Women Who Are Chronic Lack of Energy With Incidence of Low Birth Weight at Palibelo Public Health Center - FITRIYAH, NUR (Yayasan Pendidikan Intan Cendekia, 2021)
The low nutritional status of pregnant women during pregnancy can have various adverse impacts on pregnant women and babies, one of which is babies with low birth weight (LBW). LBW babies have a 10-20 times greater chance of dying than babies born with sufficient weight. This study aims to describe the nutritional status of pregnant women who lack chronic energy with the incidence of low birth weight at Puskesmas Palibelo. This research is a descriptive study using secondary data. The sample was pregnant women from the first trimester to the third trimester in the Palibelo Community Health Center from January to September 2020 with a total of 50 respondents. Data collection with medical data records. The results of data analysis: a. Age category: respondents aged 20-35 years with the highest nutritional status of chronic lack of energy as much as 62.0% and with LBW as much as 14.0%. B. Education category: respondents whose chronic lack of energy is based on the highest education are those with high school education as much as 68.0%, 18.0% with low birth weight. C. Economic status category: respondents whose chronic lack of energy is based on the highest economic status are respondents with moderate economic status as much as 70.0%, 12.0% who experience LBW. The results of this study indicate that age, education and good and mature economic status do not provide a definite possibility that a pregnant woman will avoid chronic lack of energy and the incidence of LBW.Keywords : Pregnant Women, Chronic Lack of Energy, Low Birth Weight